Praktik Perkawinan Wanita Hamil Di Sleman (Studi Di Desa Pondokrejo Tempel) - Navis Syahadah (UIN Sunan Kalijaga Yogyakarta, 2018)
This study examines the problem of pregnantmarriage in Pondokrejo Village by focusing onunderstanding and practice among the people. Thepractice of pregnant marriage that occurred among thepeople of Pondokrejo Village was motivated as in othersocieties by extramarital pregnancies. The practice ofpregnant marriage is regulated in Article 53Compilation of Islamic Law which confirms thatmarriage in a pregnant state is permitted. Article 53Compilation of Islamic Law which states that womenwho are pregnant may be married to men and themarriage does not need to be repeated. The practice ofpregnant mating in Pondokrejo Village has its ownuniqueness, namely the repetition after the birth of thebaby. With this the compilers are interested inexamining the reasons why the people in PondokrejoVillage are married in a state of pregnancy andunderstanding and practice of pregnant marriages.In this study the compilers used field research.With the research the compiler came to the location tomake observations to the people in Pondokrejo Villageto find out the community's understanding andpractices that occur in the community towardspregnant marriage. In addition to observationobservations, the author also conducted interviews withseveral parties related to the issue such as the Head ofHamlet, Chairperson of the RT, Chairperson of the RW,the community and the perpetrators. The approachused in this study is the legal sociology approach toobserve how the understanding of the community and the practice of pregnant marriage in Pondokrejo Villageare then linked to the legislation that governs this. Tofind out why the community allows marriage andpractices that exist in the community by looking at therecording and repetition of the marriage.This study reveals that the people of PondokrejoVillage in allowing pregnant marriages because of thecover-up of disgrace, obtaining child status and maleresponsibility for impregnating her. The publicunderstanding of pregnant marriages is grouped intotwo, namely, the first group that allows the practice ofpregnant marriages and the second group whichprohibits marriage in a pregnant state. Whereas relatedto the practice of pregnant marriage the authors foundthat along with the understanding of the community canbe translated into three, namely prohibition, the matingpermits pregnant on condition and without conditions,while the acquisition is done by recording and having apostnatal remarriage.